Using automatic speech recognition to transcribe voice messages from African farmers - Farm Radio International (Communication Initiative, 2024)
How do you gather qualitative information from thousands of people, quickly and at scale? That's a question Farm Radio International, a communication for development organization that uses interactive radio as its primary tool to reach and amplify the voices of rural Africans, has an answer to: On Air Dialogues. This on-air polling process uses Interactive Voice Response technology in tandem with Farm Radio's Uliza Interactive suite of services. Radio programs spark discussion about topics, then listeners call Uliza Interactive to leave their responses - both qualitative and quantitative - to questions.